Debating personal health budgets. (February 2016) - Alakeson, Vidhya; Boardman, Jed; Boland, Billy; Crimlisk, Helen; Harrison, Charlotte; Iliffe, Steve; Khan, Masood; O'Shea, Rory; Patterson, Janet
Summary: Personal health budgets (PHBs) were piloted in the National Health Service (NHS) in England between 2009 and 2012 and were found to have greater positive effects on quality of life and psychological well-being for those with mental health problems than commissioned service, as well as reducing their use of unplanned care. The government intends to extend PHBs in England for long-term conditions, including mental health, from April 2015. Given the importance of engaging clinicians in the next phase of PHB development, we provide an overview of the approach, synthesise the evidence from the national pilot and debate some of the opportunities and challenges. Balancing individual choice and recovery with concerns for risk, equity and the sustainability of existing community services is the central tension underpinning this innovation in mental health service delivery.